2020
DOI: 10.3390/agronomy10101604
|View full text |Cite
|
Sign up to set email alerts
|

Root and Agro-Morphological Traits Performance in Cowpea under Drought Stress

Abstract: Drought is responsible for major yield losses in many worldwide crops and is expected to occur more frequently due to climate change. Cowpea, one of the most drought tolerant legumes, stands as a promising crop in the future climatic context. The screening for genotypes well adapted to this constraint is an essential step to improve cowpea production. A collection of 29 cowpea genotypes (Vigna unguiculata L. Walp.) from the Iberian Peninsula and 11 other countries from worldwide regions was grown and submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 53 publications
(110 reference statements)
1
6
0
1
Order By: Relevance
“…In the study of plant adaptation processes (avoidance or tolerance) in reaction to water deficit conditions, the dynamics of the shoot and the root adjustments are considered as a significant parameter [14]. The results of this study showed that significant changes occurred in basic biomass parameters in both organs, and they are consistent with other previously reported findings [15][16][17].…”
Section: Resultssupporting
confidence: 90%
“…In the study of plant adaptation processes (avoidance or tolerance) in reaction to water deficit conditions, the dynamics of the shoot and the root adjustments are considered as a significant parameter [14]. The results of this study showed that significant changes occurred in basic biomass parameters in both organs, and they are consistent with other previously reported findings [15][16][17].…”
Section: Resultssupporting
confidence: 90%
“…Il a donc eu une allocation préférentielle de la matière sèche vers la partie aérienne (tige plus feuilles). Contrairement au cas du voandzou, les travaux réalisés par Turk et al (2004) et Santos et al (2020) ont montré que la croissance racinaire a été moins affectée que celle de la tige chez la lentille et le niébé.…”
Section: Discussionunclassified
“…Contrary reports showed a reduced uptake of N, P, K, Mg and Ca in legumes (Habibzadeh et al 2015;McCulloch et al 2021;Ullah and Farooq 2021) underwater stress which could be explained by the reduction in transpiration rates, altered membrane permeability, decline in the root-absorbing power and impaired nutrient mobility in the soil (Santos et al 2020).A greater demand of the minerals for seeds can be expected as the plant grows thus, it is expected that lower mineral content of leaves in dry seed stage rather than immature pods. Moreover, leaf nutrients content is affected by developmental stage.…”
Section: Leaf Nutrients Contentmentioning
confidence: 86%
“…However, under climate change, extreme unfavorable conditions such as drought and heat stress affect cowpea production in the arid and semi-arid regions, leading to yield loss(Venkatesh and Park 2014 ).This pattern is expected to continue as cowpea is the main grain legume of Mediterranean areas, Africa tropics and sub-tropics (Prgomet et al 2019 ). In addition, Europe is facing a deficit of about 70% of grain legumes (Santos et al 2020 ) and 60% of the current legumes producing areas in Sub Saharan Africa are projected to become unsuitable for common bean production before the end of the century (Carvalho et al 2019 ; Karapanos et al 2017 ; Keshavarz and Sadegh-Ghol-Moghadam 2017 ).…”
Section: Introductionmentioning
confidence: 99%